2022
DOI: 10.1093/jtm/taac116
|View full text |Cite
|
Sign up to set email alerts
|

Increased imported severe Plasmodium falciparum malaria involving hyperparasitaemia (>10%) in a UK hospital following relaxation of COVID-19 restrictions compared to the pre-pandemic period

Abstract: We identified and compared patients diagnosed with Plasmodium falciparum malaria at a large hospital in London, UK prior to the COVID-19 pandemic versus following relaxation of COVID-19-associated restrictions. We found that parasitaemias, rates of hyperpasitaemia and severe malaria were significantly higher in the period post-relaxation of COVID-19 restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The decreased travel activity during 2019-2020 led to a steep decline in travelassociated infections, including malaria (21). With lifted restrictions after the COVID-19 pandemic, travel activity has increased, and several European countries have recently reported serious malaria cases (22,23). In Denmark (J. Kurtzhals, personal communication, July 2021), a fatal case of P. falciparum malaria after relaxation of travel restrictions was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased travel activity during 2019-2020 led to a steep decline in travelassociated infections, including malaria (21). With lifted restrictions after the COVID-19 pandemic, travel activity has increased, and several European countries have recently reported serious malaria cases (22,23). In Denmark (J. Kurtzhals, personal communication, July 2021), a fatal case of P. falciparum malaria after relaxation of travel restrictions was observed.…”
Section: Discussionmentioning
confidence: 99%
“…As travel increases again, the number of imported malaria cases are rising. Of concern, several recent publications have highlighted an increase in severe malaria cases [ 3 , 4 , 12 ]. A report on malaria among personnel in the French Armed Forces noted an increase in severe cases in 2020 which was not attributed to an increased incidence in the cohort or decreased compliance with chemoprophylaxis [ 12 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A report from a Spanish national collaborative network also noted a significant increase in cases of severe malaria during 2020–2021 [ 3 ]. Another publication on imported P. falciparum found that parasitemia, rates of hyperparasitemia and severe malaria were significantly higher following relaxation of COVID-19 restrictions [ 4 ]. Although currently under investigation, some of the possible causes identified included delays between disease onset and diagnosis, due to fear of SARS-CoV-2 transmission in overcrowded hospital services, misdiagnosis of febrile illness as COVID-19 (cases of Plasmodium spp.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, the notified cases decreased significantly during the coronavirus disease 2019 (COVID-19) pandemic (366 notified cases in 2020) [3]. After the travel restrictions were lifted, an increase of severe malaria cases was reported [4], the reason of which remains unclear to date.…”
Section: Introductionmentioning
confidence: 99%